Introduction: STS and Disability. (January 2014) - Blume, Stuart; Galis, Vasilis; Pineda, Andrés Valderrama
What is the "conventional sense" of disability, and how do the questions addressed in this special issue of Science, Technology, & Human Values ( STHV ) differ from those inspired by Donna Haraway and the cyborg? In industrialized societies, the medical profession has authority over the determination of who should count as disabled while "assistive technologies" enable specific kinds of subject positions (in terms of personhood and competencies as well as limits). In this special issue of STHV, the focus of the essays as a whole is on the different enactments of disability, as complexity that simultaneously implicates bodies, gender, sexuality, technology, and politics. The study of disability offers scope for refinement and further articulation of many issues of long-standing concern to science, technology, and society (STS). In addition, we hope they will encourage further reflection on our field's normative engagement.